2021
DOI: 10.3390/ijerph181910315
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead Levels and Cardiovascular Disease Risk: Results from the Korean National Health and Nutrition Examination Survey

Abstract: (1) Objective: Lead, a heavy metal that exists commonly in air, soil and crops may cause chronic disease in the cardiovascular system. The purpose of this study is to investigate how blood lead levels affect cardiovascular disease in adults. (2) Study Design and Participants: It is a cross-sectional, descriptive study using data from the Korean National Health and Nutrition Examination Survey (KNHANES). Data from a total of 1929 participants, derived from the KNHANES, conducted by the Korea Centers for Disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The Korean National Environmental Health Survey, including 2,591 Korean adults, reported that blood Pb, blood mercury (Hg), and urine Hg levels were significantly correlated with dyslipidemia (23). The association between Framingham risk scores (FRS) and blood Pb levels was supported in the Korean cross-sectional study involving 1,929 participants, which showed that blood Pb levels were correlated with high systolic blood pressure, FRS, and total cholesterol (24) and with low HDL levels. Therefore, our findings support the previous evidence that blood Pb levels could increase the risk of hyperlipidemia.…”
Section: Discussionmentioning
confidence: 91%
“…The Korean National Environmental Health Survey, including 2,591 Korean adults, reported that blood Pb, blood mercury (Hg), and urine Hg levels were significantly correlated with dyslipidemia (23). The association between Framingham risk scores (FRS) and blood Pb levels was supported in the Korean cross-sectional study involving 1,929 participants, which showed that blood Pb levels were correlated with high systolic blood pressure, FRS, and total cholesterol (24) and with low HDL levels. Therefore, our findings support the previous evidence that blood Pb levels could increase the risk of hyperlipidemia.…”
Section: Discussionmentioning
confidence: 91%
“…ESA therapy carries dose-dependent clinical risk, including thromboembolism and cardiovascular disease. [30][31][32][33] Simultaneously, lead confers toxic effects on several other organs not addressed in this study, including neurocognitive [34][35][36] and cardiovascular [37][38][39] disease, both of which are disproportionately prevalent in the CKD commu-nity. Furthermore, because lead itself is nephrotoxic, 40 ongoing exposure may accelerate CKD progression 41,42 leading to a feed-forward cycle in which lead exposure drives its own accumulation due to impaired excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have also found that blood lead was associated with an increased risk of carotid atherosclerosis and hypertension (19,33). Besides clinical diseases, the side effects of blood lead were also observed in subclinical diseases, namely, several studies have demonstrated that blood lead was related to poor cardiovascular metabolic parameters, obesity, metabolic disorder and impaired left ventricular systolic function (12,16,(34)(35)(36)(37)(38). In addition to blood lead, other studies have also revealed that urine lead and dietary lead intake were positively correlated with CVD risk factors, metabolic syndrome or allcause mortality (39,40).…”
Section: Discussionmentioning
confidence: 99%